Evaluation of the impact of public support from the point of convergence criterion - Sobotková, Lucie; Sobotka, Martin (My University, 2016)
The article deals with the ex post evaluation of the impact of drawing funds from operation programme to achieve the convergence in the field of tourism after the entry of the Czech Republic to the EU. The evaluation of achievement of convergence or divergence between regions is based on the beta and sigma convergence indicators that enable the evaluation of the development of time series of relevant indicators (in this case, the indicators in the field of tourism). This evaluation was carried out within the regions associated into the cohesion regions NUTS II. The investigation follows the fact that the achievement of convergence within the regions was demonstrated only in a few cases of evaluated indicators of tourism. The convergence in all cases, therefore, has not been proved. In some cases, was rather recorded the tendency to divergence between the regions. Also, the relationship between the aid granted and the annual growth of the chosen indicators has not been achieved in all cases. Relevant factors, that have an impact on the explored area, is more and their weight is likely higher than in the case of drawing support from the EU funds.
Zhodnocení dopadů veřejné podpory z pohledu kritéria konvergence
Keywords: convergence; divergence; regional operational programme; EU subsidies; konvergence; divergence; regionální operační program; podpora EU